Physical activity levels and patients' expectations of physical activity during acute general medical admission. Issue 5 (May 2014) - Cattanach, N.; Sheedy, R.; Gill, S.; Hughes, A.
Abstract Bedrest during hospital admission is common and might be harmful. There is scarce published evidence that quantifies physical activity levels and expectations regarding physical activity of general medical patients during an acute inpatient stay. The current study aimed to investigate physical activity levels and expectations regarding physical activity in general medical patients at a large Australian teaching hospital. A convenience sample of 24 general medical patients was observed at 10‐min intervals in one day between 8:00 and 17:00 and their physical activity status recorded. Participants completed a questionnaire regarding their expectations of physical activity during illness and hospital admission. Patients were observed to be in bed 51% of the time, were sitting out of bed 43% of the time, were standing 1% of the time and were walking 5% of the time. One third of participants (n = 8) were not observed to walk during the observation period. Questionnaire data indicated that nine (38%) participants expected to remain in bed while in hospital. General medical patients had low levels of physical activity during their hospital stay, which was consistent with many participants' expectations of appropriate activity when in hospital. If physical activity is an important part of acute general medical patient management, then patient expectations of the appropriateness of physical activity need to be addressed and methods to increase physical activity implemented.